#### Answer

The required value of $ fof\left( -1 \right)$ is $\underline{3}$.

#### Work Step by Step

From the given graph:
$ fof\left( -1 \right)=f\left( f\left( -1 \right) \right)$
where, $ f\left( -1 \right)=0$
So,
$\begin{align}
& fof\left( -1 \right)=f\left( f\left( -1 \right) \right) \\
& fof\left( -1 \right)=f\left( 0 \right) \\
& =3
\end{align}$
Since, $ f\left( 0 \right)=3$
$ f\left( f\left( -1 \right) \right)=3$
Therefore, the value of $ f\left( f\left( -1 \right) \right)=\underline{3}$.